Analisa Interaksi Pegawai Pada CV. Diamond Printing Menggunakan Social Network Analysis (SNA) - Budi Santoso; Danny Manongga; Irwan Sembiring (Elkom : Jurnal Elektronika dan Komputer, 2021)
Diamond Printing is one of the largest offset printing companies with 32 years of experience and is located in the city of Surabaya, East Java. Data from HRD managers explained that there was no report from observations related to employee work effectiveness in terms of coordination and synergy between employees as seen from the communication and collaboration relationships. The absence of data related to the effectiveness of the performance of CV employees. Diamond Printing in terms of communication network mapping is one of the obstacles faced by HRD in determining KPI (key performance indicator). By using the Social Network Analysis (SNA) method with the help of UCINET 6 software, it is hoped that some employees will have advantages, especially in collaboration and communication in group network structures. There are three parameters used in SNA, including: degree centrality, closeness centrality, and betweenness centrality. This study involved 104 respondents (the entire population) with a sampling technique using snowball sampling and a questionnaire as a means of collecting data. The results of this study indicate that most of the collaboration and communication network interactions are dominated by manager level employees and department heads. Based on these findings, an innovation is needed from all stakeholders from CV. Diamond Printing in developing effective communication methods between its members.